THE INFLUENCE OF PREDISPOSITIVE AND ENABLING FACTORS ON ANTENATAL CARE VISIT COMPLIANCE IN THE NEW NORMAL ERA - Qonitatul Mawaddah; Ita Yuliani; Sri Rahayu (SEAJOM: The Southeast Asia Journal of Midwifery, 2023)
New normal is a change in behavior by always implementing health protocols in all aspects of life/activities, such as keeping a distance, wearing masks, having hand washing facilities and ethics when coughing/sneezing. During this period, there were many restrictions on almost all health services, such as services for pregnant women, childbirth, postpartum and family planning. This causes antenatal care services for pregnant women to be one of the services affected, both in terms of access and quality. Antenatal care visits can be influenced by several factors including: predisposing factors in the form of: age, education, occupation, parity, spacing of pregnancies, knowledge of pregnant women and attitudes of pregnant women and enabling factors in the form of: distance to place of residence, family income and information media. The purpose of this study was to determine the effect of predisposing and enabling factors on adherence to antenatal care visits in the new normal era. The research design is analytic observational with a retrospective approach. The instrument in this study was the respondent's medical record. This study used 92 respondents who were taken by simple random sampling technique. The results of the chi square test obtained a p-value of 0.001 (<0.05) on the influence of predisposing factors on compliance with ANC visits and obtained a p-value of 0.383 (>0.05) on the effect of enabling factors on adherence to ANC visits. Conclusion: there is an influence of predisposing factors on adherence to antenatal care visits in the new normal era and there is no effect of enabling factors on adherence to antenatal care visits in the new normal era